THE EFFECT OF TRAINING, WORK MOTIVATION AND WORK ENVIRONMENT ON THE PERFORMANCE OF PELITA BANGSA UNIVERSITY EMPLOYEES - Nurul Ariffaeni Islami; Irfan Afriantoro (SEAN Institute, 2022)
The purpose of the study was to find out 1. The effect of training on employee performance, 2. The effect of work motivation on employee performance and, 3. The effect of the work environment on employee performance at Pelita Bangsa University. The results of the analysis using the regression equation are as follows: Y = 4,596 + 257 + 263 + 385. The t test showed that obtained the calculated t value (X1) 2098, (X2) 2.388, (X3) 4.777 then the calculated sig t value of (X1) 0.040, (X2) 0.020, (X3) 0.000 compared to the sig value of 0.05, so the working hypothesis Ha was accepted and the null hypothesis Ho was rejected. The obtained value of R (Correlation coefficient) is 0.807 and the value of R2 (coefficient of Determination) is 0.65. The conclusion of the results of this analysis states that the proposed research hypothesis is accepted because training has a significant effect on employee performance and has a positive effect on employee performance, work motivation has a significant effect on employee performance and has a positive effect on employee performance, the work environment has a significant effect on employee performance and has a positive effect on employee performance.